Microwave-assisted synthesis of 5-substituted 1H-tetrazoles via [3+2] cycloaddition over a heterogeneous Cu-based catalyst: application to the preparation of N-13-labelled tetrazoles - Joshi, Sameer M.; Mane, Rasika B.; Pulagam, Krishna R.; Gomez-Vallejo, Vanessa; Llop, Jordi; Rode, Chandrashekhar (New Journal of Chemistry, 2017)
The [3+2] cycloaddition between various nitriles and sodium azide proceeds smoothly in the presence of a new Cu-II catalyst in N-methyl-2-pyrrolidone (NMP) to give the corresponding 5-substituted 1H-tetrazoles. The desired tetrazoles were obtained in high yields within 3-30 min by employing controlled microwave heating. The reaction most probably proceeds through the activation of the nitrile groups by the Cu-II species, followed by a successive [3+2] cycloaddition with the sodium azide. The good performance of the catalyst enabled the preparation of selected tetrazoles labelled with the positron emitter nitrogen-13 even under conventional heating. The short reaction time, simple work-up procedure, and recyclability of the catalyst are advantages of the method reported here.

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water